PENATALAKSANAAN NON-FARMAKOLOGI NYERI POST OPERASI PADA PASIEN DEWASA - Bambang Sumantri; Haryanto; Imran; Suriadi (LPPM Universitas Abdurrab, 2026)
Postoperative pain is a common problem experienced by adult patients and may adversely affect physical and psychological recovery if not managed optimally. Non-pharmacological approaches constitute an important component of complementary nursing interventions in postoperative pain management. This study aimed to map the types and characteristics of non-pharmacological interventions used in the management of postoperative pain among adult patients through a scoping review approach. A literature search was conducted using the Garuda, Google Scholar, ScienceDirect, and PubMed databases, covering publications from the past five years. Article selection followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow. Of the 236 articles identified, 10 articles met the inclusion criteria and were analyzed descriptively. The findings of the scoping review indicated that the most frequently reported non-pharmacological interventions included music therapy, deep breathing techniques, and massage therapy. These interventions were reported to be associated with reduced pain intensity, increased relaxation, and support for patient comfort and sleep quality. The mechanisms discussed in the literature included cognitive distraction, emotional regulation, activation of the parasympathetic nervous system, and stimulation of the endogenous analgesic system. In conclusion, non-pharmacological interventions play a role as complementary therapies in postoperative pain management among adult patients. Nevertheless, variations in study design and limitations in sample size remain challenges in strengthening the existing evidence base. Further research employing more robust methodologies, as well as exploration of the caregiver’s role in therapy implementation as part of continuing care, is still required.